Value orientations of vkontakte users with different strategies for meanings transferring - Pavel N. Ermakov; Ekaterina E. Belousova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper presents the results of a study of strategies for transferring the meanings and the value orientations of young people in social networks. The Internet is so firmly rooted in our everyday life that we can no longer imagine our life without it. It is penetrating into an increasing number of human life spheres, becoming the environment in which communication, educational and work processes, leisure and shopping take place. Its hard not to notice that the youth audience is especially interested in the virtual environment. The Internet and, in particular, social networks are becoming the environment that influences the formation and development of society, the dissemination of ideas, news, trends. On the Internet, one can observe both the amazing consolidation of users who are able to create a news agenda, and the disunity of many contradictory judgments, meanings and forms of their presentation. The purpose of this study is to identify the strategies for the translation of meanings that Internet users resort to when commenting on posts on social networks, and to study the value orientations of young people using various strategies for the translation of meanings. The study includes the authors questionnaire, the method of diagnosing M. Rokichs value orientations, methods of mathematical statistics (H-Kruskal-Wallis criterion, 22-criterion). Terminal and instrumental values characteristic of the 6 strategies of meanings transferring have been determined; the strategies most often used by users with abstract and concrete terminal values are revealed. The research helps to understand how the transferring of meanings takes place in a network and according to which characteristics of the value sphere users with different strategies for the meanings transferring differ.